Apuntes para una aproximación diacrónica de las competencias y su interpretación en el contexto educativo. (2021)
The term competence has crossed the recent history with a multiplicity of meanings, senses and interpretations, jact that has generated a diversity of uses and adaptations in the diffirent disciplines, tbeories and approaches.. However, this word that has gone over the right path to beeome a conceptofgreat demand is used nowadays in two wide study fields, the labor one and the educational one. And is precisejy in this lastfteld where the pretensions of this artícle are centered, since it startsjrom the intention of knowing more about the widespread conjecture around the development and learning of the competences. A quick historicalrevisionallows to know severalapproaches in which the term competences has been used; mainjy, in the fteld of the social-s.ciencesand, speciftcaljy , in the educationa! environment. Anyway, the fact of recognizjng that it is a polisémico and controverted term m diffirent areas mates even more its study and dialeetic concept in thefteld of the education, 'ustjor being in the center of this discussion the complex and enigmatic human being. The present document is divided in two parts, in theftrst is pretended to do a diachronic approach of the term, without necessarijy being understood as a "state-of-the-art" of the term, its relation with the purposes of formation and its coveling jrom the multiple meanings jrom the context in whch this can be evaluated. For the second part,, a reflection of the competences in the edueative environments, its development and learning jor the educable suiject is done, as well as an approach to the rejemngs of euaiuation that allow us to state a hypotheszS about the development and learning of the competences that jacilitate to condude some theoretical elementsjavorable for his academic operacionalization.